Difusi Produk Bioteknologi “Probiotik” Untuk Meningkatkan Produksi Ternak Ruminansia di Desa Lelede Kecamatan Kediri, Lombok Barat - Arafatul Ulfa; Mahfud Akbar; Muhamad Ali; Jihad Akbar (Universitas Mataram, 2019)
The community of Lelede Village, Kediri District, West Lombok Regency, mostly cultivate goats and cattle. However, the cultivation of both types of livestock is still done traditionally using grass and agricultural waste as feed. From that case, the addition of microorganisms which has the ability to digest fiber is very important in order to optimize the digestion process of the feed. Probiotics are certain microorganisms that can help digestion and can minimize the presence of disease. In this activity the production and the use of probiotics has been diffused to improve the livestock production performance in Lelede Village, Kediri District, West Lombok Regency. The activity began with socialization of probiotics, training of probiotics production, and its used for ruminants. The training material consisted of the process of making probiotics started from measuring the dosage of ingredients, making inoculum, until the production of probiotics in fermentors. For the training, 35 farmers have been involved. The probiotics produced are then distributed to farmers for later given to livestock either through feed or drink water.